Continuity of Care Approach for High-Risk Pregnant Women: Its Impact on Family Independence in Childbirth Preparation - Sholikah, Siti Mar'atus; Wardani, Novita Kusuma; Harumi, Ani Media (Journal La Medihealtico, 2025)
This study aims to analyze the effectiveness of high-risk pregnant women's assistance based on Continuity of Care (COC) on family independence in preparing for safe and planned childbirth. This study used the Quasi Experimental Design method, with the One Group Pretest-Posttest design, the population of all high-risk pregnant women and their families (202 people) in the Wonoayu District of Sidoarjo, the research sample was some high-risk pregnant women and their families (134 people) with a simple random sampling technique with inclusion criteria; High-risk pregnant women and their families, have a KIA book and live in the Wonoayu Sidoarjo Health Center area. Research instruments with questionnaires and KIA books. Data analysis with the Wilcoxon Signed Rank Test. Significance value p = 0.001, namely α <0.05, meaning that COC-based high-risk pregnant women's assistance is effective in increasing family independence in preparing for safe and planned childbirth. COC-based high-risk pregnant women's assistance is effective in increasing family independence in preparing for safe and planned childbirth. COC-based high-risk pregnant women's assistance is effective in increasing family independence in preparing for safe and planned childbirth.